Theoretical end experimental evaluation of perforations effect on sound insulation - Khrystoslavenko, Olga; Grubliauskas, Raimondas (International Conference “Environmental Engineering”, 2017)
To design a sound-absorbing panel, it is important to identify factors that affect the maximum sound absorption of low, middle and high frequency sounds. Perforation effect is very important for the noise-reducing and noise-absorbing panels. Perforations are often used for sound reduction. Experimental data shows that the perforation is very effective to absorb low-frequency noise. In the presented study, influence of perforation coefficient of noise reduction was analyzed with theoretical and experimental methods. The experiments were conducted in noise reduction chamber using an perforated construction with glass wool filler. Sound reductions index of 15 dB indicates good acoustic properties of the panel.